Analysis of Customary Village Law Enforcement in Joint Decree (SKB) Sampradaya Non-Dresta - Putu Ulandari Sri Lestari; I Gusti Agus Mas Rwa Jayantiari (International Journal Labs, 2022)
This study aimed to find out the analysis of customary village (Desa Adat) law enforcement in Joint Decree (SKB) Sampradaya Non-Dresta. The method used was a normative legal research method using a statutory and history approach. The customary village is the closest government system to its territory. It has the autonomy to regulate and manage its household. The existence of Sampradaya, especially Hare Krishna Bali is the duty of the customary village to keep realizing the customary village kasukerta (harmony). If there is a violation of the Sampradaya ritual in the customary village territory, it will be the responsibility of each customary village. In addition, the results of violantion can be reported to the Customary Village Council (MDA), a party that can cooperate with the customary village. The issuance of SKB by PHDI and MDA cannot be intended as something that bond the customary village because it has an authoritative authority as the constitution of customary village autonomy.